Flower Structures of Averrhoa dolichocarpa Rugayah & Sunarti - Tri Yuni Indah Wulansari; Seni Kurnia Senjaya; Inggit Puji Astuti (Journal of Tropical Biodiversity and Biotechnology, 2022)
Hermaphrodites are believed to be the ancestral characters of flowering plants. However, plants have developed spatially and functionally in arrangements to reduce the chances of self-fertilization. One well-known spatial arrangement is heterostyly. This arrangement is found in almost all Oxalidaceae species, including Averrhoa spp. The question that arises with the discovery of two new species of Averrhoa is how the spatial flower arrangement of the new species is. This study observed flowers of A. dolichocarpa to prove heterostyly of the species. We also compared morphological and anatomical characteristics among flower morphs of A. dolichocarpa. Three flower morphs, S-morph, M-morph, and L-morph, were observed, proving that A. dolichocarpa is tristyly. Morphologically and anatomically, there was no significant difference between the three flower morphs. Differences in morphometry were found in three flower morphs. In addition to the notable differences in style length in heterostyly, differences in ovary height between flower morphs were observed. The flower morphology and anatomy of A. dolichocarpa are similar to that of A. carambola and A. bilimbi and follow the general pattern of Oxalidaceae.